2020
DOI: 10.1002/hep.31231
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus–Telomerase Reverse Transcriptase Promoter Integration Harnesses Host ELF4, Resulting in Telomerase Reverse Transcriptase Gene Transcription in Hepatocellular Carcinoma

Abstract: Background and Aims Hepatitis B virus (HBV) integrations are common in hepatocellular carcinoma (HCC). In particular, alterations of the telomerase reverse transcriptase (TERT) gene by HBV integrations are frequent; however, the molecular mechanism and functional consequence underlying TERT HBV integration are unclear. Approach and Results We adopted a targeted sequencing strategy to survey HBV integrations in human HBV‐associated HCCs (n = 95). HBV integration at the TERT promoter was frequent (35.8%, n = 34/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 34 publications
0
57
0
Order By: Relevance
“…36 Recent studies have shown that the binding of E74-like ETS transcription factor 4 (ELF4) to chimeric HBV EnhI in the TERT promoter region is the molecular mechanism of HBV integration-mediated telomerase activation. 37 It is worth noting that HBV DNA integration has been found in approximately 70% of HCC patients with occult HBV infection (OBI) in recent years, mainly involving the virus X and preS/S genomic regions. 38,39 HBV DNA gene integration is associated with changes in tumor suppressor genes, mutations in the p53 gene, and genomic instability in HCC patients with OBI.…”
Section: Hbv Dna Integrationmentioning
confidence: 99%
“…36 Recent studies have shown that the binding of E74-like ETS transcription factor 4 (ELF4) to chimeric HBV EnhI in the TERT promoter region is the molecular mechanism of HBV integration-mediated telomerase activation. 37 It is worth noting that HBV DNA integration has been found in approximately 70% of HCC patients with occult HBV infection (OBI) in recent years, mainly involving the virus X and preS/S genomic regions. 38,39 HBV DNA gene integration is associated with changes in tumor suppressor genes, mutations in the p53 gene, and genomic instability in HCC patients with OBI.…”
Section: Hbv Dna Integrationmentioning
confidence: 99%
“…To date, 19 independent studies have identified a total of 435 integrations of HBV-DNA in the TERT gene, and 62.99% (274/435) of HBV-DNA integration occurs in the promoter region of TERT. As HBV-DNA insertion into the TERT promoter was associated with an increased TERT mRNA expression and a more aggressive tumor behavior in HCC, 36 it is hypothesized that the recurrence of HBV-DNA integrations into the TERT promoter region in HCC could be due to the potential growth advantage and clonal expansion capacity rendered by the augmented TERT expression. [37][38][39] In this study, TERT was inserted by HBV-DNA four times in three different ICC samples.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, HCC integrations have been found in TERT, MLL4, CCNE1, and CCNA2, etc. (e.g., [35,36]), mostly in promoter/intron regions, as well as in DNA sequences for non-coding RNAs [37]. However, unlike the situation in the woodchuck model, well-defined relationships between integration and tumorigenesis have been found in less than half of human HCCs analyzed so far.…”
Section: Hbv Dna Integration As a Risk Factor For Hccmentioning
confidence: 99%